Pengaruh Infeksi Laten Toksoplasmosis Terhadap Lama Rawatan Skizofrenia Episode Pertama - Rina Amtarina; Andriza Andriza; Nurfi Pratiwi; Sarah Udayana (Fakultas Kedokteran Universitas Riau, 2021)
Toxoplasma metabolism effect can rise the dopamine production which aggravate the simptoms of schizophrenia. Some of the research reports that patients which diagnosed with schizophrenia with positive IgG Toxoplasma need longer duration of treatment and may relapse. This study was conducted by cross sectional method on 51 patients with first episode schizophrenia, including acute and temporary psychotic disorder, in Tampan Mental Hospital – Pekanbaru. IgG anti-toxoplasma were detected on the patients at the first treatment in 2019, and then the length period of treatment and the recurrence frequency were monitored in the first year of the course of the disease. From the chi square test result, we can conclude that there’s no effect of IgG Toxoplasma on the duration of treatment on the first episode schizophrenia patients as well as the recurrence frequency which monitored in the first year course of the disease (p>0.05). There’s no effect of IgG Toxoplasma on the duration of treatment on the first episode schizophrenia patients as well as the recurrence frequency.